Bi-racial identity pains in Lawrence Hill`s, any known blood - Abbas, Hussein Ali; Mani, Manimangai (Center for Resource, Research and Publication Services, (CRRPS) India, 2017)
Establishing a sense of identity by an immigrant in exile is a hard issue. It becomes harder when an immigrant marries from another race or is born to racially different parents. The colonial practice of bringing people of different races into a certain society has brought about mixed marriages and bi-racial children. This study discusses how mixed marriages and bi-racial children affect the immigrants’ sense of their identity. The discussion is based on the novel titled Any Known Blood (1997) which was written by a Canadian author named Lawrence Hill. Hill is born to a Black father and a White mother. Most of his works is dominated by the issues of bi-racial identity. The main objective of study is to discuss how a mixed marriage and bi-racial children spark a sense of identity crisis among the African Canadians. The discussion intends to examine the events and characters in the novel of Any Known Blood (1997) by Lawrence Hill.